1992
DOI: 10.1111/j.1460-9568.1992.tb00115.x
|View full text |Cite
|
Sign up to set email alerts
|

GAP‐43 mRNA in Rat Spinal Cord and Dorsal Root Ganglia Neurons: Developmental Changes and Re‐expression Following Peripheral Nerve Injury

Abstract: The expression of growth-associated protein GAP-43 mRNA in spinal cord and dorsal root ganglion (DRG) neurons has been studied using an enzyme linked in situ hybridization technique in neonatal and adult rats. High levels of GAP-43 mRNA are present at birth in the majority of spinal cord neurons and in all dorsal root ganglion cells. This persists until postnatal day 7 and then declines progressively to near adult levels (with low levels of mRNA in spinal cord motor neurons and 2000 - 3000 DRG cells expressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 63 publications
8
58
1
Order By: Relevance
“…While the expression of GAP-43 mRNA and protein is strongly upregulated in DRG neurons after peripheral nerve transection (Verge et al, 1990;Chong et al, 1992;Andersen and Schreyer, 1999), it has been shown that dorsal root injury does not induce GAP-43 expression in the affected DRG (Chong et al, 1994;Ramer et al, 2001;Schreyer and Skene, 1993). In this study, we report that uninjured cervical DRG from p75 ϩ/ϩ and p75 -/-adult mice display low levels of GAP-43 protein, reflecting the fact that GAP-43 expression in adult rat DRG is heterogeneous and reduced compared to neonatal levels (Chong et al, 1992;Verge et al, 1990). Twenty-eight days after rhizotomy, however, there was a clear increase in GAP-43 protein levels in both p75…”
Section: Expression Of Gap-43 Protein In Drgmentioning
confidence: 99%
“…While the expression of GAP-43 mRNA and protein is strongly upregulated in DRG neurons after peripheral nerve transection (Verge et al, 1990;Chong et al, 1992;Andersen and Schreyer, 1999), it has been shown that dorsal root injury does not induce GAP-43 expression in the affected DRG (Chong et al, 1994;Ramer et al, 2001;Schreyer and Skene, 1993). In this study, we report that uninjured cervical DRG from p75 ϩ/ϩ and p75 -/-adult mice display low levels of GAP-43 protein, reflecting the fact that GAP-43 expression in adult rat DRG is heterogeneous and reduced compared to neonatal levels (Chong et al, 1992;Verge et al, 1990). Twenty-eight days after rhizotomy, however, there was a clear increase in GAP-43 protein levels in both p75…”
Section: Expression Of Gap-43 Protein In Drgmentioning
confidence: 99%
“…GAP-43 is highly expressed in the embryonic and early postnatal spinal cord with almost undetectable levels by P29 [120]. Following peripheral conditioning lesions, lower motor neurons and dorsal root ganglia sensory neurons dramatically upregulate GAP-43 mRNA and levels remain elevated for 5 to 10 weeks [121]. This increase in GAP-43 expression does not occur following lesion of the central branch of dorsal root ganglia sensory neurons, suggesting a potential role for GAP-43 in the regenerative response, which occurs specifically following peripheral lesion [122].…”
Section: Intrinsic Capacity To Regeneratementioning
confidence: 99%
“…We, therefore, examined the effect of stem cell transplantation on the expression of a number of genes known to be affected by peripheral nerve injury. Growth-associated protein GAP-43 is a molecule that is up-regulated in sciatic motor neurons and L4-L6 DRG neurons after sciatic nerve injury [55] and has been implicated as one of the several important mediators of peripheral nerve regeneration [6]. Typically, treatments such as electrical stimulation and growth factor administration, which stimulate regeneration, are associated with elevated levels of GAP-43 [56,57].…”
Section: Stimulated Asc Enhance Nerve Repairmentioning
confidence: 99%